Avaliação da supressão de Aedes aegypti (Linnaeus, 1762) (Diptera: Culicidae) com a armadilha Gravid Aedes Trap em condições de campo no município de Piumhi, Minas Gerais - Luiz Henrique Vieira Mota (2018)
New methodologies for vector control are essential to prevent recent outbreaks and reemergence of arboviruses transmitted by Aedes aegypti and Aedes albopictus. Among adult mosquito control methods, the use of adult mosquito traps has been evaluated in several countries with promising results, including Brazil. Recently, the Gravid Aedes Trap (GAT) has been developed and used in several countries as a new tool for the monitoring of adults of Aedes. The present study aimed to evaluate for the first time, the GAT as a tool to suppress Aedes aegypti females in field conditions by mass trapping. The experiment was carried out in three experimental areas of Piumhi city (MG) during the epidemiological weeks of 10-22 of 2016. Each area consisted of 25 blocks that were monitored throughout the study by the 1 GAT per block. The treatments consisted of control (no trap), 1GAT/property and 2GAT/property. The entomological indices MAFI (Mean of Aedes Females Index) and GPI (GAT Positivity Index) were used to evaluate the effect of mass trapping. The experiment consisted of evaluating the entomological indices during the periods of pre-intervention (no trap), intervention (use of traps for mass collection) and post intervention (removal of mass trapping). The results showed that from the total of mosquitoes caught, the greatest abundant specie was Ae. aegypti (81.5%), compared with Ae. albopictus (3.2%) and Culex sp. (15.3%), whereas the sex ratio was 98.6% females and only 1.4% males. Thus, these results showed the specificity of the GAT trap in trapping female Ae. aegypti. It was observed that the entomological indices were significantly reduced during the intervention and post intervention period in mass trapping areas (1 or 2GAT/property). There was a positive correlation for temperature and negative for precipitation with a one-week lag of the mass trapping areas with 1 and 2GAT/property. This work reports for the first time the presence of the zika virus in the Piumhi city, but through infected mosquitoes caught by GAT trap specially in the mass trapping areas. We conclude that the GAT trap is a tool that can be used in control programs Ae. aegypti by mass trapping. However, future studies should be conducted in several municipalities under diverse conditions to evaluate if that mass trapping by GAT can control and prevent arboviruses transmission by Ae. aegypti.